Emerging Religious Consciousness—A Cosmotheandric Understanding of Reality in the Light of Sophiology of Some Russian Theologians towards an Eco-Theology - Buitendag, Johan (Religions, 2022)
Intercultural theology is increasingly a major subject matter of 21st-century scholarly inquiry. This results in an interreligious discourse and encounter at different levels. However, gone are the days when the aim is to identify or even to fuse certain overlapping magisteria. A linguistic-cultural approach takes us beyond mergers or grand unified theories. To speak of reality as a whole is not to talk about the whole of reality. Creatio continua, the radical newness of each moment and phase unfolds in unpredictable ways. The ecological crisis of planet earth has forced all responsible researchers to engage with the Anthropocene by establishing space for a common earth religion. Through ressourcement, it appears that the sophiology of theologians of the Russian Silver Age (e.g., Solovyov, Bulgakov, and Florensky) can open up a vista in the spirit of aggiornamento to a meta-religious approach recognising the infinite capacity of humanity to transcend particularised religious identities and so belong in different ways too, with, and in God. In the end, sophiology is a form of progressive Christianity that puts together philosophy and faith by promoting an ecological public theology that is concerned about raising society’s awareness about creation as material nature.